EFEKTIVITAS PROGRAM MEMBACA 15 MENIT BERBANTUAN CERITA BERGAMBAR TERHADAP LITERASI SISWA - annisa; Dela Puspita Sari (Jurnal Dharma PGSD, 2026)
Abstract: Reading literacy is a fundamental skill that is highly important for elementary school students, yet the reading literacy level of students in Indonesia remains relatively low. This study aims to determine the effectiveness of a 15-minute reading program assisted by picture story book media in improving the reading literacy skills of third-grade students at SDN 28 Tanah Periuk. The study used a quasi-experimental method with a pretest-posttest design. The research subjects were 25 third-grade students at SDN 28 Tanah Periuk, selected using a purposive sampling technique. Data were analyzed descriptively and inferentially using a paired sample t-test. The results showed that the average pretest score of 64.56 increased to 83.56 in the posttest, an increase of 19.00 points. Learning mastery increased from 36% (9 students) in the pretest to 96% (24 students) in the posttest. The paired sample t-test results showed t-count = 16.78 > t-table = 2.064, with a significance value of p = 0.000 < 0.05, indicating that the 15-minute reading program assisted by picture story book media was proven effective in improving the reading literacy skills of third-grade students at SDN 28 Tanah Periuk. Keyword : Literacy, reading, story, picture, effectiveness.